Perbandingan Self-Efficacy dan Hasil Belajar pada Pembelajaran Fisika Berbantuan Edmodo dan Line - Wayan Suana; Erni Wahyuningsih; Feriansyah Sesunan; Erimson Siregar; Margaretha K. Sagala (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
This study aimed to describe the differences in self-efficacy and student learning outcomes between Edmodo and Line-assisted physics learning. This study applied a quasi-experimental with samples taken by purposive sampling. The sample is 59 students from two classes, one was assisted by Edmodo learning management system and the other was by Line instant messaging app. Self-efficacy data were taken using a scale consisting of 20 items, learning outcomes data were collected using test of 20 multiple choice questions. The data analysis technique was conducted using independent sample t-test. The test results for self-efficacy obtained the value of sig. (2 tailed) of 0.009 which means that there is a significant difference in self-efficacy between the Edmodo class and the Line class. However, in the aspect of higher-order cognitive abilities and inquiry skills, there were no significant differences between the two classes. For learning outcomes data, it is obtained the value of sig. (2 tailed) overall is 0.000. That is, there is a significant difference in learning outcomes between the two classes. However, if viewed per level, the difference is only seen at the low cognitive level, while at the high cognitive level, there is no significant difference in the two classes. These results indicate that learning physics assisted by MIM Line has the potential to improve learning outcomes and self-efficacy. Furthermore, learning physics assisted with MIM Line is seemed better than assisted by LMS Edmodo.